Effect of Financial Performance and Business Risk on Capital Structure - FARAH NUR AZIZAH Farah; Firdayetti (Journal of Applied Management and Business, 2022)
The purpose of the following research is to analyze and obtain the results of profitability, cash flow and business losses on company profits and changes in financial structure. The following research is a quantitative analysis research using descriptive method. The following research population is all transportation and logistics companies listed on the Indonesia Stock Exchange for the three period. The sampling method used is purposive sampling and the research method used in the following research is multiple linear analysis, classical hypothesis testing and hypothesis testing using the Statistical Package for Social Sciences (SPSS) version twenty two program to test hypotheses. The following research results show that the effect of debt and business risk/loss has a significant effect on financial planning or is called capital structure, while profit is not so significant.